BUILDING RESILIENCE IN STUDENTS: A UNIFIED APPROACH TO OVERCOMING CHALLENGES - Abdunazarov Abdulkhay; Akmaral Ermatova; Shahlo Xatamova (Bright Mind Publishing, 2025)
Resilience is a critical life skill that empowers students to navigate challenges, setbacks, and uncertainties. In today’s fast-paced and ever-changing world, fostering resilience is no longer optional—it’s essential. At Nurafshon Presidential school, we believe resilience is built through a unified effort involving leadership, staff, and counseling services. Together, we create an environment where students can thrive emotionally, socially, and academically. This article highlights how the vice director, HR representative, and school counselor collaborate to build resilience in students, equipping them to overcome obstacles and achieve their full potential.
Keywords: Resilience, Leadership,Growth, Mindset,Perseverance, Safe Spaces, Anti-Bullying Policies, Inclusive Practices, Reflection.